Morbidity and mortality results of COVID-19 variant in COVID-19 positive patients treated in the intensive care unit - KASAPOĞLU, UMUT SABRİ (My University, 2023)
Aim: COVID-19 has the potential to affect many systems and organs, resulting in serious clinical symptoms that necessitate admission to the intensive care unit. The purpose of this study was to examine the relationship between CAR, other laboratory findings, comorbidities, and mortality in patients infected with the original SARSCoV-2 or other variants.Materials and Methods: The data of 368 patients admitted to the intensive care unit with COVID-19 pneumonia between March 2020 and July 2021 were analyzed. These patients were divided into two groups. The first group included [(OC) Original SARSCoV-2 ] COVID-19 infected patients in the first period of the pandemic. The second group [(OV) Other Variants] included patients with COVID-19 infection due to other variants.Results: The mean age (Mean +/- SD) in the OC group was 69.79 +/- 11.77 years. The mean age of the patients in OC was higher than in the OV group (p=0.001). The most common comorbid disease in both groups was Hypertension (54.1%, 48.8%), followed by diabetes mellitus (DM) (30.2%, 31.6%). The mean age of the survivors in the OC and OV groups was lower (64.53 +/- 13.04, 57.85 +/- 16.78, p=0.001, p=0.001, respectively). It was observed that albumin and lymphocyte counts were lower in the deceased, while LDH, CRP, Neutrophil, procalcitonin, NLR and CAR were higher (p<0.05). Discussion: In critically ill COVID-19 patients, high CAR and NLR are good predictors of mortality. In the period when the variants were dominant, the mean age of the patients and the length of stay in the intensive care unit were lower.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; COVID-19; Variant; CAR; NLR; SARS-COV-2 VARIANTS